Increasing the stability of hydrogen production in the wind energy-hydrogen system through the use of synthetic inertia of the wind turbine; International Journal of Hydrogen Energy; Vol. 47, iss. 91 - Razzhivin I. A. Igor Andreevich (2022, 2022)
Title screen